2024
DOI: 10.1097/hjh.0000000000003664
|View full text |Cite
|
Sign up to set email alerts
|

Associations between lipid-lowering drugs and pregnancy and perinatal outcomes: a Mendelian randomization study

Runfang Wang,
Jing Zhao,
Li Li
et al.

Abstract: Introduction: Mounting evidence has indicated that maternal dyslipidemia is associated with adverse obstetric outcomes, and the actions of lipid-lowering drugs in pregnant women remain controversial. Hence, this study aimed to appraise the causal relationship of lipid-lowering drugs [hydroxymethylglutaryl-coenzyme reductase (HMGCR) inhibitors, PCSK9 inhibitors, and NPC1L1 inhibitors] with pregnancy and perinatal outcomes using drug-targeting Mendelian randomization analysis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…We utilized identical methodologies for single nucleotide polymorphisms (SNPs) selection as described in a previously published study that identified gene targets for lipid-lowering drugs. We conducted LD pruning by using the clump_data() function implemented in TwoSampleMR (https://github.com/MRCIEU/TwoSam-pleMR) R package [1,5,6]. The SNPs employed as instrumental variables in our study were consistent with those used in other studies (Huang et al, Zhao et al, Qin et al), thus mitigating the risk of reducing the standard error of the observed association or narrowing the confidence interval beyond the true value [1,3,4].…”
Section: Reply To 'Accuracy In Drug Target Mendelian Randomization Of...mentioning
confidence: 99%
See 3 more Smart Citations
“…We utilized identical methodologies for single nucleotide polymorphisms (SNPs) selection as described in a previously published study that identified gene targets for lipid-lowering drugs. We conducted LD pruning by using the clump_data() function implemented in TwoSampleMR (https://github.com/MRCIEU/TwoSam-pleMR) R package [1,5,6]. The SNPs employed as instrumental variables in our study were consistent with those used in other studies (Huang et al, Zhao et al, Qin et al), thus mitigating the risk of reducing the standard error of the observed association or narrowing the confidence interval beyond the true value [1,3,4].…”
Section: Reply To 'Accuracy In Drug Target Mendelian Randomization Of...mentioning
confidence: 99%
“…First, in this study, we referred to the published literature and set the threshold of linkage disequilibrium (r 2 < 0.3), in order to avoid the influence of strong linkage disequilibrium on the results [1][2][3][4]. We utilized identical methodologies for single nucleotide polymorphisms (SNPs) selection as described in a previously published study that identified gene targets for lipid-lowering drugs.…”
Section: Reply To 'Accuracy In Drug Target Mendelian Randomization Of...mentioning
confidence: 99%
See 2 more Smart Citations